Pragmatics and Semiotics - Brandt, Per Aage (Revista Acta Semiotica, 2021)
Meaning is determined by both immanent and transcendent semiotic structuring : it is both conceptual and contextual. The recursion of semiosis makes it possible to understand and theorize this open but non-chaotic relation between minimal, medial, and maximal sign structures and the experiential lifeworld that infuses social systems with meaning and lets cultural, semiosic, and mental content develop as a continuity. Semiotics and pragmatics are interconnected, and their bonds are indissoluble ; if cut off, pragmatics would become a part of psychology and semiotics a specialty of linguistics. The cognitive theory of mental spaces and conceptual blending needed a semiotic and, as suggested in the article, a semio-pragmatic grounding in order to grow out of its initial format as a philosophical daydream. The model explained here shows how situational and experiential contributions intervene in the sense-making.